# How to solve for r₂?

how to solve for r₂ in:

R(r₁ + r₂) = r₁r₂

### 4 Answers

Relevance

- Jeff AaronLv 72 years ago
R(r₁ + r₂) = r₁r₂

Rr₁ + Rr₂ = r₁r₂

r₁r₂ - Rr₂ = Rr₁

r₂(r₁ - R) = Rr₁

r₂ = Rr₁ / (r₁ - R)

NOTE: If r₁ = R, then r₁ = R = 0, and r₂ can be ANYTHING.

- llafferLv 72 years ago
R(r₁ + r₂) = r₁r₂

Start by distributing the R:

Rr₁ + Rr₂ = r₁r₂

Now move all terms with r₂ to one side and all other terms to the other:

Rr₁ = r₁r₂ - Rr₂

Factor out the r₂:

Rr₁ = r₂(r₁r₂ - R)

And divide:

r₂ = Rr₁ / (r₁r₂ - R)

- 2 years ago
R * (r[1] + r[2]) = r[1] * r[2]

R * r[1] + R * r[2] = r[1] * r[2]

R * r[1] = r[1] * r[2] - R * r[2]

R * r[1] = r[2] * (r[1] - R)

R * r[1] / (r[1] - R) = r[2]

Still have questions? Get answers by asking now.